Automorphisms of fusion systems of finite simple groups of lie type - Broto, Carles, 1959-; Møller, Jesper; Oliver, Robert, 1949- (Memoirs of the American Mathematical Society, 2019)
For a finite group G of Lie type and a prime p, we compare the automorphism groups of the fusion and linking systems of G at p with the automorphism group of G itself. When p is the defining characteristic of G, they are all isomorphic, with a very short list of exceptions. When p is different from the defining characteristic, the situation is much more complex, but can always be reduced to a case where the natural map from Out(G) to outer automorphisms of the fusion or linking system is split surjective. This work is motivated in part by questions involving extending the local structure of a group by a group of automorphisms, and in part by wanting to describe self homotopy equivalences of the p-completion of the classifying space BG in terms of Out(G).